Rabo-de-Bacalhau building type morphology: data to a transformation grammar-based methodology for housing rehabilitation - Eloy, S. (2014)
This paper is done in the scope of a research in which a housing rehabilitation was methodology is developed to meet contemporary functional and ICT requirements. The methodological hypothesis is to use description grammars, shape grammars, and space syntax as tools for identifying and encoding the principles and rules underlying the adaptation of existing dwellings to meet new requirements. ‘Rabo-de-bacalhau’ building type was used to develop the transformation grammar-based rehabilitation methodology. This paper focuses on the characterization (functional, constructive, stylistic, and cultural) of the case study buildings at the time of construction and nowadays. The process to transform dwellings and the possibility of generating designed solutions that meet the user’s requirements is discussed at the end of the paper.